Returning ryegrass to continuous cropping soil improves soil nutrients and soil microbiome, producing good-quality flue-cured tobacco - Zhou, Hanjun; Zhang, Mingjie; Yang, Jiahao; Wang, Jing; Chen, Yulu; Ye, Xiefeng (Frontiers in Microbiology, 2023)
The widespread and continuous cultivation of tobacco has led to soil degradation and reduced crop yields and quality. Green manure is an essential organic fertilizer that alleviates obstacles to continuous cultivation. However, the plant–soil microecological effects of green manure on flue-cured tobacco cultivation remain unclear. Thus, a positioning trail including two treatments, chemical fertilizer application only (treatment NPK) and chemical fertilizer application with turning ryegrass (treatment NPKG) was conducted, and the effect of ryegrass returning on the soil physicochemical properties, soil microbiome, crop yield, and quality of flue-cured tobacco in continuous cropping soil were investigated. Results showed that returning ryegrass to the field increased the thickness of soil humus layer from 13 cm to 15 cm, reduced the humus layer soil bulk density to 1.29 cm3/g. Ryegrass tilled and returned to the field increased soil organic matter content by 6.89–7.92%, increased rhizosphere soil available phosphorus content by 2.22–17.96%, and converted the soil non-exchangeable potassium into potassium that was available for plant absorption and utilization. Ryegrass tilling and returning to the field increased the potassium content of middle leaves of flue-cured tobacco by 7.69–10.07%, the increased potassium content in flue-cured tobacco was accompanied by increased total sugar, reducing sugar, and the ratio of reducing sugar to nicotine, which facilitated the harmonization of the chemical composition of cured tobacco leaves. Moreover, the increased number of markedly improved operational taxonomic units enhanced the complexity of the soil bacterial community and its compactness after ryegrass tillage and their return to the field. The available potassium, available phosphorus, total potassium content, pH, and sampling period of the rhizosphere soil had considerable effects on the rhizosphere microbial. Ryegrass tilling and returning to the field changed the soil microbiome, which increased the abundance of bulk soil Proteobacteria, rhizosphere soil Fibrobacterota, and microbes with anti-pathogen activity (Lysobacteria, Sphingomonas, Chaetomium, and Minimedusa); and reduced the abundance of pathogenic fungi Neocosmospore genus in the soil. In brief, ryegrass returned to the field, improved soil microecology and restored soil nutrients, and established a new dynamic balance of soil ecology, thereby improving the quality of cultivated land and the quality of flue-cured tobacco.